Life Skills Training: A Nursing Perspective - Regina Shoba Dass; Ravi Sankar (RGUHS Journal of Nursing Sciences)
Collaboration with other medical staff patients and family members as well as the ability to think critically and act quickly are all essential in the nursing profession. The nursing job is demanding and nurses need the ability to quickly adjust to new circumstances. Most experts think that life skills are most useful when applied to matters of personal health and interpersonal relationships. Skills that help young nurses maintain a healthy mental state and perform competently under pressure are included. Self-awareness empathetic understanding creative problem solving interpersonal relationships clear and persuasive communication sound decision making and the ability to manage stress and emotions are all essential life skills. Having strong life skills is essential for success in the healthcare industry. Being emotionally mentally and physically healthy is essential for a nurses ability to do their job.